Fabrication and Characterization of High-Optical-Quality-Factor Hybrid Polymer Microring Resonators Operating at Very Near Infrared Wavelengths - R. Morarescu; P. K. Pal; N. T. Beneitez; J. Missinne; G. V. Steenberge; P. Bienstman; G. Morthier (IEEE Photonics Journal, 2016)
In this paper, we present a new fabrication method for large-area hybrid polymer microring resonators using a rib waveguide configuration with a minimum residual layer down to 40 nm by ultraviolet (UV) nanoimprint lithography. In a first step, a negative photoresist (SU8-2) patterned by photolithography on an SiO 2/silicon wafer was used as a master mold. Flexible soft molds using perfluoropolyether (PFPE)-based elastomers for high-resolution replica molding are explored in the imprinting process flow. High-quality devices with $Q$ -factors up to 39 000 and finesses up to $F \sim 14$ were demonstrated for very-near infrared wavelengths (around 900 nm). Finally, we report that the resonances can be thermooptically tuned by 0.05 nm/°C at 896 nm, thus demonstrating that, at shorter wavelengths, the fabricated microring resonators are less sensitive to temperature change, compared with longer wavelengths. The results of this paper demonstrate the capability of our method to fabricate optical devices with high performance for operation in a single mode at wavelengths where cheap light sources are available and water absorption is much lower than at far-infrared wavelengths. Because of this, it is expected that the fabricated structures have high potential for biosensing applications.